Relationship Between Depressive Symptoms and Health Status in Peripheral Artery Disease: Role of Sex Differences. Issue 16 (18th August 2020) - Jelani, Qurat‐ul‐ain; Mena‐Hurtado, Carlos; Burg, Matthew; Soufer, Robert; Gosch, Kensey; Jones, Philip G.; Spertus, John A.; Safdar, Basmah; Smolderen, Kim G.
Abstract : Background: The association of depressive symptoms with health status in peripheral artery disease (PAD) is understudied. No reports of differential impact on women have been described. Methods and Results: The PORTRAIT (Patient‐Centered Outcomes Related to Treatment Practices in Peripheral Artery Disease Investigating Trajectories) registry enrolled 1243 patients from vascular specialty clinics with new or worsening PAD symptoms. Depressive symptoms were assessed at baseline and 3 months using the 8‐Item Patient Health Questionnaire (score ≥10 indicating clinically relevant depressive symptoms). Disease‐specific and generic health status were measured by Peripheral Artery Questionnaire and EQ‐5D Visual Analogue Scale at baseline and 3, 6, and 12 months. An adjusted general linear model for repeated measures was constructed for baseline and 3‐, 6‐, and 12‐month health status outcomes by depressive symptoms at baseline. Differences by sex were tested with interaction effects. The mean age was 67.6±9.4 years with 38% (n=470) women. More women than men (21.1% versus 12.9%; P <0.001) presented with severe depressive symptoms. In the adjusted model, patients with depressive symptoms had worse health status at each time point (all P <0.0001). Results were similar for EQ‐5D Visual Analogue Scale scores. The magnitude in 1‐year change in health status scores did not differ by sex. Depressive symptoms explained 19% of the association between sex differences in 1‐year Peripheral Artery Questionnaire summary scores. Conclusions: Women with PAD have a high burden of depressive symptoms. Depressive symptoms were associated with a strikingly worse disease‐specific health status recovery path over the year following PAD diagnosis in men and women. Developing and testing interventions to address depressive symptoms in PAD are urgently needed. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01419080.